A SNARE and specific COPII requirements define ER-derived vesicles for the biogenesis of autophagosomes. Issue 6 (2nd June 2016) - Lemus, Leticia; Goder, Veit
ABSTRACT: The endoplasmic reticulum (ER) is a major source for the generation of autophagosomes during macroautophagy. Our recent work in yeast shows that particular ER-derived vesicles are generated for the biogenesis of autophagosomes. These vesicles not only incorporate a SNARE protein that is largely ER-resident under nonstarving conditions, but also display COPII requirements for ER-exit that differ from conventional cargo-transporting vesicles. Our results suggest that specific intracellular traffic is launched at the ER for the transport of membranes to sites of autophagosome formation.